An empirical analysis on the effect of OFDM parameters to the performance of wireless communication system via USRP-based transceiver - Muslimin, Jusnaini; Asnawi, Ani Liza; Ismail, Ahmad Fadzil; Khairolanuar, Muhamad Haziq; Jusoh, Ahmad Zamani; Hamid, Rosyati (Science and Engineering Research Support Society, 2017)
The configuration of parameters for OFDM scheme in standards such as the 802.11, WiMAX and LTE are varied accordingly to each system specifications. This paper offers findings from an experimental analysis carried out using wireless OFDM transceivers set-up. Experimental evaluations are indeed very useful in order to guesstimate the likely performance of any said system. Among particular system performances of interest include throughput and errors. This can be noteworthy attempt as it provides fundamental understanding and knowledge in justifying what should be the best configuration. The study had examined and quantified the effect of varying select parameters namely the modulation schemes, FFT length, and sampling rate. The use of USRP hardware as the communication testbed was extensively explored during the study. USRP sets can certainly be emerging tools for students and researchers alike to realize proof of concepts by exploiting programmable software-defined radio platforms.